2015
DOI: 10.3390/scipharm84030547
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Anticonvulsant Activity of Extracts and Protopine from the Fumaria schleicheri Herb

Abstract: The present study aimed to investigate the role of several biologically active compounds from Fumaria schleicheri Soy.-Will. in anticonvulsant models. The flavonoid fraction, alkaloid fraction, individual alkaloid protopine, and polysaccharide-protein complex were isolated from the Fumaria schleicheri herb and studied along with Fumaria schleicheri dry extract in mice with pentylenetetrazole-induced seizures. According to empirical results, the expressed anticonvulsant effect of Fumaria schleicheri dry extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The existing scientific reports cite anticonvulsant activity, especially for F. schleicheri Soy.-Will. [ 27 , 28 ]. No scientific data about polyphenols exists on F. jankae to date, as it is an endemic species, present only in a specific geographic region of Romania.…”
Section: Introductionmentioning
confidence: 99%
“…The existing scientific reports cite anticonvulsant activity, especially for F. schleicheri Soy.-Will. [ 27 , 28 ]. No scientific data about polyphenols exists on F. jankae to date, as it is an endemic species, present only in a specific geographic region of Romania.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey of some of the chemical principles found in the fractions of C. adiantifolia mentioned above reveals the medicinal value of the plant species. Protopine; an alkaloid, has been reported for its anticonvulsant activity, 20 microtubule-stabilizing effects, 21 antiinflammatory activity reducing effects, 22 neuroprotective effects, [23][24] anticholinesterase effects, 25 etc. Sanguinarine compounds have been reported for anticancer, [26][27] anti-osteoporosis, [28][29] and norsanguinarine has been reported for antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
“…In a pentylenetetrazol-induced seizure mouse model, with sodium valproate as the reference, protopine showed some anticonvulsant activity, significantly prolonged the latency of seizures, shortened the duration of convulsions, and significantly reduced the severity of convulsions. In addition, the anticonvulsant effect of protopine (0.005, 0.05 mg/kg) was dose-dependent [ 71 ]. Kardos et al found that protopine (0.1, 1, 10 μM) enhanced the binding of 3H-gamma-aminobutyric acid (3H-GABA) to rat brain synaptic membrane receptors, increased GABA-mediated Cl − influx, led to membrane hyperpolarization, decreased membrane excitability, and exerted its sedative and anticonvulsant effects [ 72 ].…”
Section: Pharmacological Activities Of Protopinementioning
confidence: 99%